Association Between Hypertension, Dipping Status, and ACE and AGTR1 Gene Polymorphisms in Adolescents with Type 1 Diabetes - Smiljka Kovacevic; Maja Jesic; Vera Zdravkovic; Stefan Djordjevic; Jelena Miolski; Vladimir Gasic; Marina Jelovac; Milena Ugrin; Sonja Pavlovic; Branko Subosic (Biomedicines)
Objectives: This study aims to show the distribution of angiotensin-converting enzyme (ACE) rs1799752 (I>D) gene insertion/deletion (I/D) polymorphism and angiotensin II receptor type 1 (AGTR1) rs5186 (A>C) gene polymorphism in adolescents with hypertension (HT) and type 1 diabetes (T1D), as well as its association with hypertension and the diurnal variation of mean blood pressure (dipping phenomenon). Methods: A cross-sectional study was conducted involving 118 adolescents diagnosed with T1D who underwent clinical and laboratory investigations, genetic analyses, and 24 h ambulatory blood pressure monitoring. The genotype frequencies were compared between adolescents with HT and those with normal blood pressure. Additionally, the genotype frequencies were compared between dippers and non-dippers. Results: Patients with HT were more likely to be female and exhibited significantly poorer glycemic control and higher triglycerides, along with increased body mass index and daily insulin dosage. The prevalence of ACE rs1799752 genotypes in the hypertensive group was 20% II, 66.7% ID, and 13.3% DD, which did not significantly differ from the normal blood pressure group with 29.1% II, 53.4% ID, and 17.5% DD (p = 0.625). The prevalence of AGTR1 rs5186 genotypes in the hypertensive group was 53.3% AC, 40% AA, and 6.7% CC, which also did not significantly differ from the normal blood pressure group with 39.8% AC, 52.4% AA, and 7.8% CC (p = 0.608). A total of 46% of the patients exhibited non-dipping phenomena. The prevalence of non-dippers among the ACE genotypes was 13% DD, 33.3% II, and 53.7% ID (p = 0.369), while for the AGTR1 genotypes, it was 50% AA, 42.6% AC, and 7.4% CC (p = 0.976). Conclusions: Our results indicate that in our adolescents with T1D, clinical and metabolic factors such as higher body mass index, triglycerides, suboptimal glycemic control, and female gender are more indicative of the development of hypertension than ACE and AGTR1 gene polymorphisms. A potential reason for this finding could be the young age of the patients or the relatively small size of the study group. Future research involving larger sample sizes is needed to further investigate the genetic predisposition for the development of hypertension.